2017
DOI: 10.1007/s12664-017-0747-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of CRS and HIPEC in appendiceal and colorectal malignancies: Indian experience

Abstract: CRS and HIPEC can be performed with acceptable morbidity and mortality in selected patients of colorectal and appendiceal malignancies with peritoneal carcinomatosis. In addition, it is associated with better overall survival. Morbidity profile of Indian subcontinent patients is different from that of western population with hematological toxicity being the most common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 10 publications
0
15
0
3
Order By: Relevance
“…Thirty-two studies were identified evaluating different techniques for intraperitoneal chemotherapy in CPM (Table 3) [4172]. Sixteen of those studies looked at drug delivery techniques [41, 42, 4446, 49, 51, 52, 54, 55, 5860, 62, 67, 68], and 16 looked at novel pharmacological approaches for drug conveyance and therapeutic enhancement [43, 47, 48, 50, 53, 56, 57, 61, 6366, 69].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-two studies were identified evaluating different techniques for intraperitoneal chemotherapy in CPM (Table 3) [4172]. Sixteen of those studies looked at drug delivery techniques [41, 42, 4446, 49, 51, 52, 54, 55, 5860, 62, 67, 68], and 16 looked at novel pharmacological approaches for drug conveyance and therapeutic enhancement [43, 47, 48, 50, 53, 56, 57, 61, 6366, 69].…”
Section: Resultsmentioning
confidence: 99%
“…For the purpose of this study, we have retained PMP as a unified diagnosis to allow for more informative statistical analyses. Various studies have shown that survival is improved with low‐grade PMP compared to high‐grade PMP . Nevertheless, the overall management of low‐ and high‐grade PMP remains the same.…”
Section: Discussionmentioning
confidence: 99%
“…Siendo la tasa de grave morbilidad a los 60 días mayor con CRS/HIPEC que con CRS solo (24.1% vs 13.6%, respectivamente). En contraparte Gupta y otros (61) también compararon la sobrevida de pacientes tratados con CRS/HIPEC cerrada y pacientes tratados únicamente con CRS. Como resultado, la sobrevida a 4 años de la CRS/HIPEC cerrada y la CRS fue de 58.9% y 33.33%, respectivamente.…”
Section: Discussionunclassified